2004
DOI: 10.1523/jneurosci.5569-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hippocampal CA3 μ-Opioid Receptors in Spatial Learning and Memory

Abstract: The dorsal CA3 region of the hippocampus is unique in its connectivity, sensitivity to neurotoxic lesions, and its ability to encode and retrieve episodic memories. Computational models of the CA3 region predict that blocking mossy-fiber and/or perforant path activity to CA3 would cause impairments in learning and recall of spatial memory, respectively. Because the CA3 region contains -opioid receptors and receives inputs from the mossy-fiber and lateral perforant pathways, both of which contain and release op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 66 publications
(85 reference statements)
1
46
0
2
Order By: Relevance
“…The HIPPO contains a high density of opioid receptors (Mansour et al 1987) and opioids modulate learning and memory-related events in this brain region (Bramham and Sarvey 1996;Jamot et al 2003;Jang et al 2003;Simmons and Chavkin 1996). Moreover, μ-opioid receptor antagonist injections into the dorsal HIPPO impair spatial memory retrieval (Meilandt et al 2004). Thus, the suppression of S + -elicited neural activation in the HIPPO may reflect NTX-mediated dampening of learned contextual associations between environmental stimuli and drug reward, leading to reduced drug-seeking normally evoked by such cues.…”
Section: Discussionmentioning
confidence: 99%
“…The HIPPO contains a high density of opioid receptors (Mansour et al 1987) and opioids modulate learning and memory-related events in this brain region (Bramham and Sarvey 1996;Jamot et al 2003;Jang et al 2003;Simmons and Chavkin 1996). Moreover, μ-opioid receptor antagonist injections into the dorsal HIPPO impair spatial memory retrieval (Meilandt et al 2004). Thus, the suppression of S + -elicited neural activation in the HIPPO may reflect NTX-mediated dampening of learned contextual associations between environmental stimuli and drug reward, leading to reduced drug-seeking normally evoked by such cues.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous early and recent studies demonstrated that a flat retrograde amnesia was induced by lesions of dHC and the entire HC at 0.5-3.5 months in watermaze memory retention (Bolhuis et al, 1994;Mumby et al, 1999; logical changes found in CA3 stratum oriens (Ramirez-Amaya et al, 2001) and may indicate involvement of the CA3 autoassociative network in recent (Nakazawa et al, 2002(Nakazawa et al, , 2003Meilandt et al, 2004) as well as in long-term memory storage and recall. Mapping data support the idea that DG is not only involved in memory encoding but also participates in memory retrieval (Nanry et al, 1989;Lisman, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclodextrin is a cyclic sucrose array that increases drug solubility but is inert and secreted rapidly (see Wall and Messier, 2000), and injection of this vehicle had no effect (compared with other control groups) on anxiety or activity measures. Meilandt et al (2004) demonstrated that injections of FNA could depress MOR binding in the hippocampus after such injections by as much as 49% at 24 h, and decreases persisted for up to 11 days (Meilandt et al, 2004). This dose of FNA in the nucleus accumbens can also block the effects of DAMGO-induced feeding at 24 h (Ragnauth et al, 2000).…”
Section: Drugs and Microinjectionsmentioning
confidence: 95%